Nabonidus, as-Silaʿ, and the Beginning of the End of Edom - Crowell, Bradley L. (Bulletin of ASOR, 2007)
The collapse of the Iron Age polity of Edom is often attributed to the western campaign of the Babylonian king Nabonidus, who traveled through Edom en route to the desert oasis of Tayma. The campaign is mentioned in several Babylonian texts, and his entrance into Edom is typically dated to 553 B.C.E., based on several fragmentary lines in the Nabonidus Chronicle. With the discovery and publication of a heavily eroded rock relief of Nabonidus at as-Silaʿ in the mountains of southern Jordan, it is confirmed that Nabonidus campaigned through the region of Edom. This article argues that, based on the few fragmentary lines of the accompanying inscription, the attack of Nabonidus on Edom can be more precisely dated to his fifth year, or 551 B.C.E.